PROBLEMATIS TERMINOLOGI PADA APLIKASI TIK TOK SEBAGAI MEDIA SARANA EDUKASI DAN HIBURAN DI KALANGAN MAHASISWA ILMU KOMUNIKASI FDK UIN SUSKA RIAU - Jummaulana, Hari; Sartika, Sartika; S, Ermairel (Ensiklopedia of Journal, 2025)
In 2024, especially in Indonesia, the development of communication and information technology has experienced very rapid development, which has become a popular culture in Indonesia. Currently, one of the most famous social media in the current era is TikTok social media. TikTok is a social media created in 2016 by the Chinese company ByteDance, which was initially a place for users to express themselves and hone their talents through video content, such as dancing and lip-syncing, now in 2024 TikTok presents useful, inspiring, and motivating video content. The use of TikTok social media has been widely used by students as a medium to fulfill their information needs. This study aims to determine how TikTok social media is used as a means of education and entertainment for Communication Science students at the Sultan Syarif Kasim State Islamic University, Riau. The results of the study show that human perception of technology such as TikTok social media provides benefits and is profitable from all types of video content shared on social media. In addition, the video content on TikTok can affect feelings and it depends on the type of content available. Video content uploaded on Tiktok social media can affect emotions depending on what kind of content is desired and what kind of content appears on the Tiktok homepage. On the other hand, the less good or less beneficial thing about this social media is the age of the audience where all ages can see and watch freely content that they should not be allowed to see because on Tiktok hoax information can quickly spread that can be easily believed by other Tiktok users. Keywords: Social Media, Tiktok, Benefits, Education